Safety and feasibility of home-based transcranial alternating current stimulation in youths with 22q11.2 deletion syndrome - Latrèche, Caren; Mancini, Valentina; McGinn, Nova; Rochas, Vincent; Férat, Victor; Forrer, Silas; Schneider, Maude; Eliez, Stephan (Frontiers in Neuroscience, 2024)
Neurodevelopmental disorders such as attention deficit and/or hyperactivity disorder (ADHD) and schizophrenia are characterized by core impairment in executive functions (EF). Despite the development of various behavioral interventions to enhance EF, the evidence is still scarce. Alternatively, non-invasive brain stimulation tools such as transcranial alternating current stimulation (tACS) has emerged as a potential strategy to alleviate cognitive deficits. Previous studies have demonstrated the safety, feasibility, and efficacy of one single tACS session in different clinical populations. However, the effects of tACS appear limited and need to be sustained to be considered an effective cognitive neurorehabilitation tool. Recent studies have used home-based, repeated tACS sessions in individuals with neurodegenerative diseases. To our knowledge, the safety and feasibility of such an intensive protocol remains to be tested in a younger population with neurodevelopmental disorders. Using a randomized double-blind sham-controlled design, we administered home-based, repeated tACS sessions to seven individuals aged 14–25 with 22q11.2 deletion syndrome (22q11.2DS), which confers an increased risk for neurodevelopmental disorders. We aimed to assess the safety, tolerability, and feasibility of tACS. Findings from this ongoing clinical trial revealed a favorable safety profile, with frequent yet transient and mainly mild adverse effects. The intervention proved to be feasible, shown by very high adherence rates and positive user experiences. Future studies should therefore investigate whether prolonged exposure to tACS can lead to long-lasting cognitive outcomes.Clinical trial registrationClinicalTrials.gov, identifier NCT05664412.